Preparação, caracterização e estudo biológico de compostos de inclusão contendo antagonista do receptor AT1 e estatinas - Carlos Eduardo de Matos Jensen (2010)
Hypertension and hypercholesterolemia are chronic diseases and still remain one of the major public health problems in Brazil and in the world. In this context, adherence to treatment is one of the biggest problems which often cause medical complications due to incorrect use of medicines. The World Health Organization (WHO) recommends that an alternative to solve this problem is related to the formulation of drugs. WHO recommends the reduction of adverse effects, decreased number of administrations and simplification of treatment. Therefore, it is necessary to look for technological alternatives that can provide these gains and emphasizing the cyclodextrins as one of the most viable options for this. Considering the group of drugs used to hypertension treatment, valsartan, a potent inhibitor of AT1 receptors, is included in the class II of the biopharmaceutical classification system, having low bioavailability due to its reduced solubility in water. In order to improve the physico chemical and biological properties of valsartan, inclusion complex were prepared with -cyclodextrin (-CD). Cyclodextrins are cyclic oligosaccharides formed by six, seven or eight glucopyranose rings, composed of an internal hydrophobic cavity and a hydrophilic outer surface. Its main property refers to the ability of modifying the solubility and bioavailability of drugs. With the intention to increase the solubility of valsartan in the gastrointestinal tract and consequently its bioavailability. The complexes were prepared by different techniques in order to provide inclusion of guest molecule in the internal cavity of cyclodextrin. The inclusion complexes prepared between valsartan and -CD were characterized by physico-chemical techniques such as thermal analysis (TG / DTG and DSC), Fourier Transform infrared spectroscopy and intrinsic dissolution. The results showed the formation of a new supramolecular compound prepared between valsartan and -CD. The inclusion complexes were also characterized in solution using nuclear magnetic resonance (2D-ROESY) and solubility diagrams. From these results it was possible to observe the formation of a new specie with equilibrium constant in the range 111.3 M-1 and 165.4 M-1. The complexation is an exothermic process indicating the formation of intermolecular bonding like van der Waals forces and hydrogen bonds. Based on the results of nuclear magnetic resonance it was determined that the inclusion occurred by insertion of the aromatic rings of valsartan in the hydrophobic cavity of cyclodextrin. In vivo studies it was observed that inclusion complex has provided more rapid decrease in arterial pressure and maintenance of this effect for four days. The other molecules studied were the statins used for treatment of hypercholesterolemia, being chosen lovastatin and simvastatin. These drugs are included in the class II of the biopharmaceutical classification system with low bioavailability, between 10 and 20%. In an attempt to increase the solubility and dissolution rate, the drugs were complexed with -CD. The phase solubility studies revealed that the statins had their water solubility increased with different equilibrium constants. The results for simvastatin showed an equilibrium constant in the range 2340.2 M-1 e 2552.1 M-1 and for lovastatin between 289.0 M-1 e 809.4 M-1. The simvastatin inclusion was characterized as an enthalpy-driven process and for the lovastatin the complexation was an endothermic process. All systems showed a reduction in free energy. Analyzing all the results it's possible to infer that the efficacy of lovastatin and simvastatin complexation is not an easy process to be performed, due to the low solubility of these drugs in water. Exactly due to this low solubility, the insertion becomes more improbable. The solubility of the drug increases the chance of occurring inclusion. This was confirmed by conducting the freeze-drying process for valsartan complexation. All these data and studies indicate that the inclusion compounds seems to be an interesting technology for controlled release of drugs, serving as a basis for pre-formulation studies and production of new formulations, improving treatment schemes, reducing side effects and increasing the adherence to the therapy